The influence of self and social image concerns on lying - Zvonimir Bašic; Simone Quercia (Max Planck Institute for Research on Collective Goods, 2020)
We investigate the influence of self and social image concerns as potential sources of lying costs. In a standard die-rolling experiment, we exogenously manipulate self-awareness and observability, which mediate the focus of a person on their private and public selves, respectively. First, we show that an increase in self-awareness has no effect on reporting private information. This suggests that self-image concerns may be less important than previously hypothesized in the literature on lying costs. Second, we show that increasing subjects' observability, while still maintaining private information, significantly decreases the subjects' reports. We finally show in a survey experiment that respondents believe that the likelihood of a lie increases with the reported outcome and attribute negative traits to people who make high reports. This further supports reputational concerns as the explanation behind the results of our social image treatment.
Keywords: C91; D63; D82; D91; 330; honesty; truth-telling; lying; private information; self-image concerns; social imageconcerns; reputation